2023
DOI: 10.1007/s11605-023-05582-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Preoperative Pulmonary Function on Short- and Long-Term Outcomes Following Gastrectomy for Gastric Cancer

Abstract: Background Preoperative pulmonary function assessment is useful for selecting surgical candidates and operative methods and assessing the risk of postoperative pulmonary complications. However, few studies have investigated the relationship between preoperative pulmonary function and short-and long-term outcomes in patients who underwent gastrectomy for gastric cancer. Methods Of the 1040 patients with gastric cancer (stages I-III) who had undergone R0 gastrectomy between 2009 and 2020, 750 who underwent preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Moreover, they are frequently associated with multiple comorbidities and high complication rates after gastrectomy. 4,33 Physiological dysfunction, multiple comorbidities, and postoperative complications may lead to decreased 1year survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, they are frequently associated with multiple comorbidities and high complication rates after gastrectomy. 4,33 Physiological dysfunction, multiple comorbidities, and postoperative complications may lead to decreased 1year survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have shown that radical gastrectomy is feasible in selected elderly patients with GC, 3,31,32 these patients are vulnerable to and affected by various physiological dysfunctions. Moreover, they are frequently associated with multiple comorbidities and high complication rates after gastrectomy 4,33 . Physiological dysfunction, multiple comorbidities, and postoperative complications may lead to decreased 1‐year survival rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations